2005
DOI: 10.1016/j.jacc.2005.04.041
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome After Fractional Flow Reserve-Guided Percutaneous Coronary Intervention in Patients With Multivessel Disease

Abstract: In patients with multivessel disease, PCI of hemodynamically non-significant stenoses can be safely deferred, even if initially planned on the basis of the angiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(83 citation statements)
references
References 18 publications
2
79
1
1
Order By: Relevance
“…Therefore, in patients with multivessel disease the use of FFR reduced the composite rate of death, myocardial infarction, and repeat revascularization at 1 year [13]. Retrospective studies have supported similar findings with FFR guided PCI resulting in better survival rates in patients who have multivessel coronary artery disease [14,15].…”
Section: Discussionmentioning
confidence: 67%
“…Therefore, in patients with multivessel disease the use of FFR reduced the composite rate of death, myocardial infarction, and repeat revascularization at 1 year [13]. Retrospective studies have supported similar findings with FFR guided PCI resulting in better survival rates in patients who have multivessel coronary artery disease [14,15].…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have demonstrated that the treatment of patients with evidence of ischemia is beneficial and yields good mid-and long-term results; however, to revascularize based on anatomical criteria is debatable and does not seem to present any advantage in relation to the conservative treatment 1,[9][10][11] . Considering the consensus of the American College of Cardiology/American Heart Association (ACC/AHA) to justify a PCI, it is necessary to prove the existence of ischemia 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…It is known that vessels that present FFR ≥0.75 can be safely treated with conservative therapies, whereas a FFR <0.75 is a sign of myocardial ischemia and the patients, in these cases, could benefit from percutaneous or surgical revascularization procedures [9][10][11] . The aim of this study was to assess, in all patients (and lesions) submitted to PCI at the Interventionist Cardiology Service of Santa Helena Hospital do Coracao within a certain period of time, the accuracy of the angiography visual estimate (AVE) and the quantitative coronary angiography (QAT) when identifying the lesions responsible for the myocardial ischemia, comparing their results with those obtained by FFR.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Based on the results of multiple studies, it was demonstrated that patients with coronary lesions associated with a FFR value > 0.80 can be treated conservatively (i.e., without an intervention for coronary revascularization), with an evolution, in medium and long term, equivalent or even superior to that observed when patients are treated with percutaneous coronary intervention (PCI) with the aim to treat such lesions. [18][19][20] It should be emphasized that the protocol of these studies focused only groups of patients in whom FFR was used exclusively to determine whether or not to maintain an interventionist conduct hither to considered as the preferred option, based on purely angiographic aspects.…”
Section: Use Of the Methods Of Fractional Flow Reserve Measurement In mentioning
confidence: 99%